P14.12 The cost-effectiveness of tumor-treating fields in patients with newly diagnosed glioblastoma. (6th September 2019) - Armoiry, X; Auguste, P; Dussart, C; Guyotat, J; Connock, M
Abstract: BACKGROUND: The addition of novel therapy "Tumor-Treating fields" (TTF) to standard radio-chemotherapy with Temozolomide (TMZ) has recently shown superiority over conventional TMZ regimen in patients with glioblastoma. Despite the clinical benefit of TTF, there is a strong concern regarding the cost of this new treatment. A first cost-effectiveness analysis, which was published in 2016, was based on effectiveness outcomes from an interim analysis of the pivotal trial and used a "standard" Markov model. Here, we aimed to update the cost-effectiveness evaluation using a partitioned survival model design and using the latest effectiveness data. MATERIAL AND METHODS: A partitioned survival model was developed with three mutually exclusive health states: stable disease, progressive disease, and dead. Parametric models were fitted to the Kaplan-Meier data for overall and progression-free survival. These generated clinically plausible extrapolations beyond the observed data. The perspective of the French national health insurance was adopted and the time horizon was 20 years. Base case results were expressed as cost/life-years (LY) gained (LYG). Secondary analyses were undertaken, with the results presented as cost/per quality adjusted life years (QALY) gained. Last, we undertook deterministic and probabilistic sensitivity analyses. RESULTS: After applying 4% annual discounting of benefits and costs, the base case model generated incremental benefit of 0.507 LY at a incremental cost of €258, 695 yielding an incremental cost effectiveness ratio (ICER) of €510, 273 / LYG. Secondary analyses yielded an ICER of €667, 173/QALY. Sensitivity analyses and bootstrapping methods showed the model was relatively robust. The model was sensitive to TTF device costs and the parametric model fitted to the Kaplan-Meier data for overall survival. The cost-effectiveness acceptability curve showed TTF has 0% of being cost-effective under conventional thresholds. CONCLUSION: Using a partitioned survival model, uprated costs and more mature survival outcomes, TTF when compared to standard radio-chemotherapy with TMZ is not likely to be cost-effective. This has major implications in terms of access of newly eligible patients